The Impact of Intellectual Capital on Financial Performance of Companies Listed in TSE - Gholamhossein Asadi; Mariya Yokhneh Alghiaee (مطالعات تجربی حسابداری مالی, 2013)
A great change and shift from financial resources to knowledge is being experienced nowadays. Physical and financial assets are essential but not enough to reach organizational goals, instead, knowledge, technological settings, good customer relations, information systems,... those constitute organization’s Intellectual Capital, are known as key success factors in information era. It’s believed that intellectual capital, including human capital and structural capital, has important and growing role in firm’s performance and affects on it’s financial achievements. This paper examines the effect of intellectual capital and it’s components on firm’s financial performance. The essential data are taken from 1383 -1388 fiscal years’ annual reports of publicly traded firms listed on the Tehran stock exchange and 816 firm-years are studied. Results of hypotheses testing show that, VAIC has positive effect on the four financial performance indicators. Between VAIC components, capital employed efficiency has the most effect on firms’ financial performance.